Topical Application of 4′-Hydroxychalcone in Combination with tt-Farnesol Is Effective against Candida albicans and Streptococcus mutans Biofilms - Lobo, Carmélia I. [UNESP]; Barbugli, Paula A. [UNESP]; Rocha, Guilherme Roncari [UNESP]; Klein, Marlise I. [UNESP] (American Chemical Society (ACS), 2022)
Candida albicans and Streptococcus mutans interaction in the presence of dietary sucrose yields a complex biofilm with an organized and structured extracellular matrix that increases the tolerance to environmental stress, including antimicrobials. Both species are found in severe early childhood caries lesions. Thus, compounds 4′-hydroxychalcone (C135) (flavonoid intermediate metabolites), tt-farnesol (Far) (terpenoid), and sodium fluoride (F) were tested either isolated or combined as topical treatments (5 min twice daily) against C. albicans and S. mutans dual-species biofilms grown on saliva-coated hydroxyapatite discs. The biofilms were evaluated for gene expression, microbial population, biochemical components, and three-dimensional (3D) structural organization via confocal microscopy and scanning electron microscopy (SEM). The cytotoxicity of formulations was tested on the keratinocyte monolayer. C135 + Far + F promoted lower gene expression of fungal genes associated with β-glucan synthesis (BGL2, FKS1) and remodeling (XOG1, PHR1, PHR2), oxidative stress (SOD1), and drug tolerance (CDR1, ERG11) and higher expression of bacterial nox1 (oxidative and acidic stress tolerance). C135 + Far yielded less insoluble exopolysaccharides, biomass, and proteins (insoluble portion) and lower expression of BGL2, ERG11, SOD1, and PHR2. C135 + F, C135 + Far + F, and C135 rendered lower biomass, thickness, and coverage percentage (confocal microscopy). C135 + Far and C135 + Far + F maintained C. albicans as yeast morphology (SEM). Therefore, the formulations with C135 affected fungal and bacterial targets but exerted a more pronounced effect against fungal cells.